Pengaruh Teknik Relaksasi Otot Progresif Terhadap Penurunan Tekanan Darah Pada Pasien Hipertensi Di Puskesmas Mariat Kabupaten Sorong - Norma Norma; Ade Supriatna (Jurusan Keperawatan Poltekkes Kemenkes Sorong, 2018)
Effect of Progressive Muscle Relaxation Technique on Decreasing Blood Pressure in Hypertensive Patients in Mariat Health Center, Sorong Regency. Hypertension is a disease that results from an increase in systolic and diastolic blood pressure consistently above 140/90 mmHg. Hypertension is a factor that contributes to stroke deaths and factors that aggravate myocardial infarction (heart attack). The number of people with hypertension continues to increase along with the growing population, the world prevalence reaches 29.2% in men and 24% in women. This study was conducted with the aim to determine whether there is an effect of progressive muscle relaxation techniques on the reduction of blood pressure in hypertensive patients at the Mariat Health Center in Sorong Regency. In this study the researchers used the Quasi experimental Design design with a one-group pretest-posttest design approach (one pretest-posttest group). The population in this study were hypertensive patients who came to the Mariat Health Center in 2018 as many as 32 patients. While the research sample is a total population of 32 respondents. The results of the statistical test using the Paired Sample t-test obtained a value of p_value for systolic blood pressure 0,000 smaller than 0.05 and the value of p_value for a diastolic blood pressure of 0,000 less than 0.05. From the results of statistical tests show that there is an effect of progressive muscle relaxation techniques on blood pressure reduction in hypertensive patients at Mariat Health Center, Sorong Regency.